PRINTING BUSINESS PRODUCTION DEVELOPMENT PROCESS STRATEGY (CASE STUDY OF PRINTING UKM NOVA FLORIST AND ADVERTISING, LHOKSEUMAWE CITY) - Zainuddin Iba; Abdur Rasyid Zasri; Durrah Safira; Ifvac Vara Azzerah; Riska Munanda (RADJA PUBLIKA, 2022)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in national economic development, because apart from playing a role in economic growth and employment, they also play a role in distributing development results. In the economic crisis that occurred in our country several years ago, where many large-scale businesses experienced stagnation and even stopped their activities, the Micro, Small and Medium Enterprises (MSMEs) sector proved to be more resilient in dealing with the crisis. However, there are also weaknesses in MSMEs, namely accessing information is suspected to be directly related to the condition of the internal factors of MSMEs, which are overshadowed by MSMEs, which actually have a large market share internationally, and are not widely known by consumers.